Role of α- and β-adrenergic Mechanisms in the Pathogenesis of Pulmonary Injuries Characterized by Edema, Inflammation and Fibrosis - Rassler, Beate (Cardiovascular & Haematological Disorders - Drug Targets, 2013)
Adrenergic mechanisms are involved in the formation of several types of pulmonary edema (PE) such as neurogenic pulmonary edema (NPE) or PE in patients with pheochromocytoma, but also in the development of pulmonary fibrosis and pulmonary hypertension. In severe cases of PE such as in the adult respiratory distress syndrome (ARDS), PE is typically accompanied by inflammation and followed by pulmonary vascular hypertrophy and pulmonary fibrosis. Norepinephrine and other adrenoceptor agonists are known to provoke activation of proinflammatory cytokines such as interleukin (IL)-1 and IL-6. These cytokines are involved both in the pathogenesis of PE and of pulmonary fibrosis. We therefore assume that adrenergic mechanisms may have an important role in the pathogenesis of pulmonary injuries characterized by edema, inflammation and fibrosis. The contribution of adrenoceptor stimulation, particularly the distinct role of α- and β-adrenergic mechanisms, to the development of PE and pulmonary fibrosis is reviewed in this paper.
Keywords: pulmonary inflammation